CardioCx: A Health Information System for Complex and High-Risk Cardiac Procedures...20th World Congress on Medical and Health Informatics (MEDINFO), August 9-13, 2025, Taipei, Taiwan. - Guinez-Molinos, Sergio; Castillo, Benjamín; Seguel, Enrique; Gonzalez, Jaime (Studies in Health Technology & Informatics, 2025)
CardioCx is a health information system for complex and high-risk cardiac procedures designed and developed in Chile. It is currently utilized to register cardiac surgery interventions at the Grant Benavente Hospital Cardiovascular Centre in Concepción. After ongoing development, modifications, and enhancements, the registry now includes 3,415 high-risk and complex cardiac procedures (the most comprehensive database in Latin America), comprising Isolated CABG (1,732), Isolated Valves (1,207), Combined CABG + Valves (224), and Others (252). The platform adheres to the standards of global cardiac surgery registries, enabling accurate data entry, consultation, and export for clinical analysis. Its architecture ensures interoperability with HL7 FHIR and incorporates an Artificial Intelligence layer for advanced analysis.